2021
DOI: 10.11591/ijeecs.v22.i2.pp1061-1068
|View full text |Cite
|
Sign up to set email alerts
|

Mobile communication (2G, 3G & 4G) and future interest of 5G in Pakistan: a review

Abstract: <span style="font-size: 9pt; font-family: 'Times New Roman', serif;">The use of mobile communication is growing radically with every passing year. The new reality is the fifth generation (5G) of mobile communication technology. 5G requires expensive infrastructural adjustment and upgradation. Currently, Pakistan has one of the most significant numbers of biometrically verified mobile users. However, at the same time, the country lags incredibly in the field of mobile internet adoption, with just half of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The growth of new frequency bands, increased data speeds, and transmission technologies implies that alternative ways of getting things done are available for each generation of people. In the second part of 2001, the first commercial 3G networks were placed into operation, with more to be done (34). Figure:6 shows 3G wireless technology.…”
Section: Nd Generation (2g)mentioning
confidence: 99%
“…The growth of new frequency bands, increased data speeds, and transmission technologies implies that alternative ways of getting things done are available for each generation of people. In the second part of 2001, the first commercial 3G networks were placed into operation, with more to be done (34). Figure:6 shows 3G wireless technology.…”
Section: Nd Generation (2g)mentioning
confidence: 99%
“…Innovative and new ideas regarding business and mobile services are emerging with the fast-paced development of mobile technology. A study (Iqbal et al, 2020) reported that Pakistan has one of the largest mobile users based on biometrical verification. However, the country is quite behind in mobile internet related adoption, with only around, a half of mobile device users using a broadband connection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite the introduction of domestic manufacturing and increased production of mobile devices, the rate of smartphone adoption remains low. Consequently, Pakistan's potential to emerge as a dominant force in the realm of smartphones, akin to China, India, and Indonesia, is at risk of eluding them, as the aforementioned countries are poised to achieve their predetermined objectives by the year 2025 (Iqbal et al, 2020). However, the global average of broadband internet penetration is 64.6% which is higher than 52.4% (Statista, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the current global economy [1], Fifth-generation (5G) mobile communication technology has become the new norm [2]. 5G, the latest wireless internet technology, promises to revolutionize our everyday lives and corporate practices.…”
Section: Introductionmentioning
confidence: 99%